Examining English and Welsh Detectives’ Views of Online Crime - Bossler, Adam M. (International criminal justice review, 2021)
The advancement of the Internet and digital technology has enabled individuals to commit crimes affecting both virtual and real targets at will. Criminological scholarship related to cybercrime and technology-enabled offending has primarily focused on offenders and victims, calling to question how police agencies effectively respond to these incidents. Limited empirical research has largely focused on line officers, who view these cyber offenses to be less serious in comparison to traditional crimes. Research examining the perceptions of detectives and inspectors is virtually nonexistent, though they are much more likely to have an investigative responsibility to pursue offenders and engage with citizens about the offense. Thus, there is a need to understand the attitudes inspectors hold toward online crime in order to improve our knowledge of police views and inform policy makers in building effective strategies to aid their response to unique and emerging crime types. This study examined the attitudinal factors associated with online crimes and incidents using a sample of 155 inspectors from 26 local agencies across England and Wales. The implications of this study for both police detectives and law enforcement agencies are discussed in detail.